Migrating into Financial Markets How Remittances Became a Development Tool - Bakker, Matt (University of California Press, 2015)
We understand very little about the billions of dollars that flow throughout the world from migrants back to their home countries. In this rigorous and illuminating work, Matt Bakker, an economic sociologist, examines how these migrant remittances-the resources of some of the world's least affluent people-have come to be seen in recent years as a fundamental contributor to development in the migrant sending states of the global south. This book analyzes how the connection between remittances and development was forged through the concrete political and intellectual practices of policy entrepreneurs within a variety of institutional settings, from national government agencies and international development organizations to nongovernmental policy foundations and think tanks. "Migrating into Financial Markets offers a much-needed interpretation of the institutions that frame migration. In this fascinating account, Bakker shows how, unable to come up with a political solution to large-scale migration, Mexico and the United States recast migrants as private actors of economic and social development." -RUBÉN HERNÁNDEZ-LEÓN, coauthor of Skills of the "Unskilled": Work and Mobility among Mexican Migrants "Contrasting governments' developmentalist rhetoric with the way their policies are actually designed and implemented, this thoughtful study makes an important contribution to a key debate in contemporary development policy." -GAY SEIDMAN, Martindale Bascom Professor of Sociology, University of Wisconsin-Madison "Bakker offers a cautionary tale of how international policy entrepreneurs' commitment to an ideology of market fundamentalism reduced their approach to addressing the human rights of migrants in the post-9/11 world to lowering the costs of wire transfers and banking the un-banked." -DAVID SPENER, Professor of Sociology, Trinity University and author of Clandestine Crossings: Migrants and Coyotes on the Texas-Mexico Border MATT BAKKER is Assistant Professor of Sociology at Marymount University.